Narrativas, discursos e identidades: (des) encontros no Sul do Maranhão - Piovesan, Marta Helena Facco (Universidade do Vale do Rio dos Sinos, 2020)
Starting from the proposition that narratives and identities emerge from social contexts and that discursiveness is a privileged lens to investigate social practices and personal experiences, this interpretative / qualitative research aims to analyze the identities built by people born in Balsas, southern city of Maranhão. The region, located in the Legal Amazon, known as the Pastos Bons Region, since its colonization has been a favorable territory for the exploitation of land suitable for agriculture and livestock. In the 1970s, the Balsas region became the destination of many farmers, especially southern ones, when the cerrado, an ecosystem previously considered unproductive, became a fertile biome and nowadays one of the largest food producers in the Northeast. The main objective of this research is to analyze how identities, specifically from the point of view of those born in the region, are built linguistically and textually in a context of recent migration. The corpus was generated through narrative interviews with people born in Balsas and made it possible to understand how participants weave their speeches regarding the migratory process in which they are inserted, and to analyze the conceptions of identity they have built by narrating their life stories. The methodology used to achieve these propositions is the articulation of Narrative and Identity Analysis with the notion of referencing, derived from Textual Linguistics. This research takes the textual-interactive perspective to aggregate the concepts of referencing and positioning for a more comprehensive focus on the textual elements involved in the construction of the stories. It also investigates narrative from a textually and discursively constituted and organized perspective and highlights narrative analysis as a social practice shaped by multiple social contexts that lead to the construction of identities. The analyses performed on these narratives have allowed us to identify the identities in a rapidly changing environment with a multitude of individuals, where identity constructions are not unified, but always changing.
Keywords: Narrativas; Identidades; Histórias; Discurso; Migração; Narratives; Identities; Stories; Speech; Migration; ACCNPQ::Lingüística, Letras e Artes::Lingüística